Unraveling the effects of hot rolling on microstructure and mechanical properties of cold sprayed Mg/Al clad plates. (December 2022) - Ren, Yupeng; Tariq, Naeem ul Haq; Liu, Hanhui; Cui, Xinyu; Wang, Jiqiang; Xiong, Tianying
Abstract: In this work, the evolution of microstructure and mechanical properties of the cold sprayed Mg/Al clad plates were examined in detail in relation to various combinations of rolling parameters. For this purpose, three different rolling temperatures (350, 400, and 450 °C) and rolling reduction ratios (10%, 20%, and 30%) were applied to the As-Sprayed samples. The macroscopic morphology, interfacial microstructure, tensile strength, and shear bond strength (SBS) of the samples were investigated in detail. Results reveal that the ultimate tensile strength (UTS) of the samples is positively related to the rolling temperature and reduction ratio. However, high rolling temperature facilitates the formation of thick intermetallic compounds (IMCs) layer, which is harmful to the SBS. In addition, a high rolling reduction ratio promotes edge cracking in clad plates. Finally, the optimized rolling parameters (400 °C and 30%) are pinpointed, which result in the best combination of macroscopic morphology, interfacial microstructure, and mechanical properties (UTS: 392.7 ± 3.3 MPa; EL: 4.5 ± 0.1%; SBS: 91.7 ± 6.3 MPa) for the clad plate. Graphical Abstract: ga1 Highlights: Well-bonded Mg/Al clad plates were fabricated by cold spraying + hot rolling. The effects of rolling parameters were studied in detail. Rolling temperatures and rolling reduction ratios were optimized (400 °C and 30%).